Induction of chirality from ligand to the supramolecular helical packing in Mo(VI)–Ln(III) heterobimetallic complexes: Synthesis, structure and photoluminescence properties. (17th February 2016) - Das, Dhiraj; Deb, Dibakar; Sadhukhan, Dipali; Bhattacharjee, Manish
Graphical abstract: Two new isostructural heterobimetallic Mo(VI)–Ln(II) (Ln = La, Ce) complexes have been synthesized and structurally characterized by single crystal X-ray diffraction. Chiral helical supramolecular chain type packing is evident from structural analysis. Circular dichroism (CD) spectroscopy supports the homochiral nature of the complexes. Abstract: Two new isostructural heterometallic Mo(VI)–Ln(III) (Ln = La, Ce) complexes have been synthesized and characterized by FT-IR, UV–Vis spectroscopy and their structures have been determined by single-crystal X-ray diffraction analysis. Chiral helical supramolecular chain type packing is evident from structural analysis. Circular dichroism spectroscopy supports the homochiral nature of the complexes. Photoluminescence spectroscopy of the complexes along with their free ligand has been performed in the solid-state.